Family support and quality of life among stunted preschool-aged children: A cross-sectional study - Handayani, Fitri; Anwar, Syamsul; Sutini, Titin (The Journal of Palembang Nursing Studies, 2025)
Background: Stunting remains a major public health problem that not only impairs physical growth but also compromises children’s emotional, social, and cognitive development, ultimately reducing quality of life. Families play a critical role in the prevention and management of stunting by providing adequate caregiving, ensuring proper nutrition, and facilitating access to healthcare services. Understanding the association between family support and quality of life is essential for guiding effective interventions. Objective: This study aimed to examine the correlation between family support and quality of life among preschool children with stunting. Methods: A cross-sectional design with a quantitative approach was applied, involving 66 parents or caregivers of preschool children aged 36–72 months diagnosed with stunting. Respondents were selected using purposive sampling. Family support was measured across emotional, instrumental, appreciation, and informational domains, while children’s quality of life was assessed using standardized questionnaires. Data were analyzed using chi-square tests and multivariate logistic regression to identify potential confounding factors. Results: The analysis demonstrated a significant relationship between family support and quality of life (p < 0.001). Children from families providing strong support were 65.9 times more likely to experience good quality of life compared with those from families with inadequate support. Multivariate analysis revealed parental education as a confounding factor (p = 0.011), with higher educational attainment contributing to stronger family support and improved child outcomes. Conclusions: Strengthening family support and improving parental education are crucial strategies to enhance the quality of life of stunted preschool children